Epidemiology and Survival Outcomes for Eyelid Primary Malignant Melanoma: An Analysis of 1397 Cases in the SEER Database - Yi Shan; Yufeng Xu; Yuexin Lu; Menglu Chen; Jing Cao; Yijie Wang; Xiling Lin; Juan Ye (Journal of Ophthalmology, 2020)
Purpose. There has not been a recent population-based study regarding the epidemiological trend and survival of eyelid primary malignant melanoma (PMM). Our study aims to evaluate the updated incidence trends and discuss the factors affecting the survival outcomes of eyelid PMM. Methods. A total of 1397 eyelid PMM cases diagnosed between 1975 and 2016 were retrospectively identified from the Surveillance, Epidemiology, and End Results (SEER) database. Age-adjusted incidence rates and annual percent changes (APC) were calculated. Kaplan-Meier and Cox proportional hazards regression models were used to calculate survival outcomes and identify potential prognostic factors. Results. The overall age-adjusted incidence of eyelid PMM rose from 0.039 (95% confidence interval [CI], 0.012–0.088) in 1975 to 0.103 (95% CI, 0.070–0.143) per 100 000 population in 2016, with significant APC of 1.313% (p<0.001). Male subjects showed a higher average age-adjusted incidence rate than female subjects (p<0.001). Survival analyses showed that 5-year accumulative overall survival (OS) and disease-specific survival (DSS) for patients with eyelid PMM were 70.5% and 90.6%. Additionally, 10-year OS and DSS were 51.8% and 86.1%, respectively. Analyses of Kaplan-Meier survival curves with the log-rank test revealed that older age, White race, nodular melanoma, higher American Joint Committee on Cancer (AJCC) stage (II to IV), advanced stage, distant metastasis, and no-surgery treatment were associated with lower OS and DSS rates. Age, histology, AJCC stage, and stage at diagnosis were found to be independent predictors of OS and DSS in multivariate models. Conclusion. The incidence of eyelid PMM increased with significant APC and male predominance. Age, histology, AJCC stage, and stage at diagnosis might be independent predictors of prognosis, emphasizing the importance of improved diagnosis of eyelid PMM.